Final answer:
The inverse function of y = root(3)(x-2) is y = (x³) + 2 or in the form a(bx+c)³+d, it would be 1*(x³) + 2.
Step-by-step explanation:
The given function is
y = root(3)(x-2) To find the inverse of a function, we first rewrite the function in terms of x. That means we swap the roles of x and y, which gives us
x = root(3)(y-2) We then solve this new function for y, which gives us y = (x³) + 2 The inverse function of y = root(3)(x-2) is therefore y = (x³) + 2 or in the form of a(bx+c)³+d, is 1*(x³) + 2
Learn more about Inverse of a Function